Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Berbantuan Media Kubal untuk Meningkatkan Hasil Belajar Siswa - Nurlaila; Rizal, Setria Utama; Syabrina, Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the application of cooperative learning model type think pair share (TPS) assisted by cube block media (Kubal) in mathematics learning in class V MIS Fathul Iman Palangka Raya, improve student learning outcomes, and find out how much improvement in learning outcomes is achieved through the model. The method used is Classroom Action Research (CAR) with the Kemmis & Mc. Taggart model consisting of planning, action, observation, and reflection stages. The subjects of this study were 27 students of class V B at MIS Fathul Iman with data collection techniques through tests, observations, and documentation. The results of the study showed that the application of the TPS model assisted by Kubal media can create interesting, interactive learning, and is able to encourage students to think critically. Learning was carried out in two cycles and showed a significant increase. Teacher and student activities increased with very good criteria, as well as an increase in student learning outcomes from an average of 62.6 (low category) classical completeness 52% and an average to 82.6 (high category) classical completeness to 89%. The increase in the N-Gain Test value of 0.7325 (high) increased from the low category to the high category. Conclusion, the cooperative learning model of the TPS type assisted by Kubal media is effective in improving the quality of learning and students' mathematics learning outcomes. Keywords: Learning Outcomes, Kubal Media, TPS Cooperative Learning Model